Delineation of the nerve fiber bundles of the infant brain associated with aging using phase difference-enhanced imaging: a preliminary study - Fujii, Hiroyuki; Sato, Noriko; Kimura, Yukio; Sugiyama, Atsuhiko; Shigemoto, Yoko; Suzuki, Fumio; Matsuda, Hiroshi; Sasaki, Masayuki; Sugimoto, Hideharu (Japanese journal of radiology, 2020)
Purpose The purpose of this study was to evaluate the delineation of nerve fiber bundles in the brainstem and optic radiation in infants associated with aging on T1WI, T2WI, and phase difference-enhanced (PADRE) images. Materials and methods We retrospectively reviewed 21 consecutive subjects < 2 years old who underwent brain MRI without abnormal imaging findings. Two neuroradiologists evaluated the eight nerve fiber bundles in the brainstem and optic radiation using a 3-point scale focused on the contrast to surrounding brain parenchyma. We also evaluated the signal ratio of the optic radiation to surrounding white matter on PADRE for each month age. Results T2WI was able to delineate nerve fiber bundles better than T1WI at 1 month old, and the images gradually became unclear with aging. On PADRE, almost all nerve fiber bundles were unclear or invisible at 1 month old but gradually became clearer with aging. There was a significant negative correlation between age and the signal ratio of the optic radiation to surrounding white matter. Conclusions The PADRE imaging was able to delineate the nerve fiber bundles in infants, and the delineation gradually became clearer with aging. The combination of PADRE, T1WI, and T2WI would be useful for evaluation of nerve fiber bundles in infants.